2016
DOI: 10.1002/cam4.760
|View full text |Cite
|
Sign up to set email alerts
|

A miRNAs panel promotes the proliferation and invasion of colorectal cancer cells by targeting GABBR1

Abstract: MicroRNAs (miRNAs) have been implicated in the regulation of colorectal cancer. Despite the expression of miR‐17‐92 cluster in cancer has been gradually revealed, the role of each individual miRNAs in colorectal cancer still remains unclear. We studied the impact of miR‐106a/b, miR‐20a/b, and miR‐17 of miR‐17‐92 cluster on colorectal cancer cells. Real‐time quantitative polymerase chain reactions (RT‐PCR) were used to test these five miRNAs expression in colorectal cancer cell line HCT116. 3‐(4,5‐dimethyl‐2‐th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…MiR-20a promotes proliferation, invasion and the epithelial-to-mesenchymal transition (EMT) of CRC cell lines. Similar to the results in this study, miR-20a was found to downregulate matrix metalloproteinases, including MMP2 and the EMT marker E-cadherin [60][61][62][63], supporting the findings of this study, although no study has linked it with the colonization of the primary tumor to the liver. Likewise, although miR-449a deficiency was shown to promote colon carcinogenesis [64], it has not been previously linked to liver metastases.…”
Section: Discussionsupporting
confidence: 88%
“…MiR-20a promotes proliferation, invasion and the epithelial-to-mesenchymal transition (EMT) of CRC cell lines. Similar to the results in this study, miR-20a was found to downregulate matrix metalloproteinases, including MMP2 and the EMT marker E-cadherin [60][61][62][63], supporting the findings of this study, although no study has linked it with the colonization of the primary tumor to the liver. Likewise, although miR-449a deficiency was shown to promote colon carcinogenesis [64], it has not been previously linked to liver metastases.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, miR-17-5p directly targets RND3, a Rho Family GTPase that acts as tumor suppressor by promoting adhesion [ 98 ]. MiR-17 along with miR-106a/b and miR-20a/b targets GABBR1(gamma-amino-butyric acid type B receptor 1) thus promoting colorectal cancer cell proliferation and invasion [ 99 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing number of studies suggested that miRNAs affect the progression, pathogenesis, diagnosis, and prognosis of cancer [12]. miRNA was critically involved in the proliferation and invasion progress in many kinds of tumor, such as gastric cancer, pancreatic cancer, breast cancer and colorectal cancer [13-16], while there’s still not enough public research about how miRNA affect the proliferation and invasion of PAs.…”
Section: Introductionmentioning
confidence: 99%